MULHERES E CEBs EM MONTES CLAROS-MG: DESCOLONIALIDADE E EMPODERAMENTO - ROCHA, LETÍCIA APARECIDA FERREIRA LOPES (2019)
This research proposal, in the light of the decolonial theoretical contributions, with focus on the decolonial feminism and on the theory of empowerment, aims to reflect and problematize the participation and the transformations that occurred during the life trajectory of many women of the Ecclesial Base Communities (CEBs), of the Parish of São Sebastião, in the city of Montes Claros, located in the North of Minas Gerais. The selected historical section covers the decades from 1985 to 1995, considered a period of greatest effervescence and dissemination of these groups in the city. In this study, it was used the methodological resource of thematic oral history. This methodology proved to be effective and made possible to unveil the daily life of women with their struggles, achievements, learning and challenges that is expected in the peripheral urban space and the ecclesial space of the sertanejo that is still reticent to the participation of women. The guiding question of the research is if this participation can be considered decolonial and empowering, causing transformations in their life trajectories. In more specific terms, this focuses on questions such as: Has the maintenance of coloniality still prevailing within the religious practice. Initially, we assumed that the practices and actions developed at the heart of the CEBs now seemed to have contributed to new positions of the participants, which denotes decoloniality and empowerment, or have corroborated, in order to maintain the coloniality already present within them.